Analisis Bauran Pemasaran 7P Menggunakan Analisis Swot Pada Tm Project Cafe Batam - Nadya Ivana Adeline; Dailami .; Tito Pratama; Natal Olotua Sipayung (CV. ITTC INDONESIA, 2025)
The development of a healthy lifestyle is driving the emergence of integration between fitness centers and healthy food services, including the implementation of the open kitchen and bar concept. However, it is not known to what extent the food and beverage strategy implemented by cafes in the fitness center environment is able to attract interest and increase customer satisfaction. This study aims to analyze the food and beverage strategy at TM Project Cafe and assess the effectiveness of the implementation of the open kitchen and bar concept in supporting operations and customer experience. This study uses a type of qualitative descriptive research with a case study approach. Data was collected through direct observation, semi-structured interviews with management, chefs, baristas, customers, and fitness members, menu documentation and space layouts, and simple questionnaires related to customer satisfaction. Data analysis was carried out through the process of reduction, presentation, and conclusion drawn, and strengthened by SWOT analysis to assess the position of TM Project Cafe's food and beverage strategy in healthy café competition. The results of the study show that TM Project's food and beverage strategy focuses on natural ingredients, healthy menus, and interactive services. The application of the open kitchen and bar concept has been proven to increase transparency, trust, and customer satisfaction as it provides a visual experience and direct interaction during the serving process. Overall, this concept effectively supports TM Project Cafe's food and beverage strategy and strengthens its image as a provider of healthy lifestyle services.